Evaluation of oxidative stress, immune system and mineral concentrations in milk and serum of cows with clinical and subclinical mastitis naturally infected by staphylococcus aureus - Serdal KURT; Funda ESKI; Leyla MIS; Pinar AYVAZOGLU DEMIR (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
The aim of this study was to investigate effect of Staphylococcus aureus on oxidative stress status (TAS, TOS, OSI), immune system (IL-1β, IL-6, TNF-α), and mineral (Mg, Fe, Zn, Cu, Na and Ca) concentrations in milk and serum of cows with mastitis. The cows were allocated to three groups according to mammary health status as follows: healthy (Group 1), clinical (Group 2) and subclinical mastitis cows (Group 3). IL-1β levels in serum and milk increased in Group 2 compared to Group 1 and Group 3 (P<0.001; P<0.05). Milk IL-6 level was greater in Group 3 and Group 2 than in Group 1 (P<0.01). Blood TNF-α (P<0.001), TOS and OSI levels (P<0.01) were higher in Group 2 than other groups. Milk TNF-α level increased and blood TAS level decreased in Group 2 compared to Group 1 (P<0.05). Milk TOS (P<0.01) and OSI (P<0.05) levels increased in Group 3 compared to Group 1. Blood and milk Mg levels increased in Group 1 (P<0.05) and Group 2 (P<0.001), respectively. Milk Fe (P<0.01) and Na levels were greater in Group 2 (P<0.001). Blood Zn level was lower in Group 2 compared to Group 3 (P<0.05). While blood Cu level decreased in Group 1 compared to other groups, milk Cu level decreased in Group 3 compared to other groups (P<0.001). In conclusion, S. aureus had significant effects on oxidative stress, cytokine and mineral levels in milk and blood serum of cows with clinical and subclinical mastitis. However, since there were specific changes only in milk OSI and IL-6 levels according to other parameters, it is thought that milk IL-6 and OSI levels may be a diagnostic tool in the detection of subclinical mastitis.